2018
DOI: 10.12688/f1000research.13115.1
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in understanding evolution of the placenta: insights from transcriptomics

Abstract: The mammalian placenta shows an extraordinary degree of variation in gross and fine structure, but this has been difficult to interpret in physiological terms. Transcriptomics offers a path to understanding how structure relates to function. This essay examines how studies of gene transcription can inform us about placental evolution in eutherian and marsupial mammals and more broadly about convergent evolution of viviparity and placentation in vertebrates. Thus far, the focus has been on the chorioallantoic p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…There are alternative explanations that must be considered, not in the least that the mouse and human placenta differ substantially both structurally and transcriptionally ( Carter, 2018 ; Soncin et al, 2018 ), which could prevent the accurate modelling of this disorder in mice. The DelTel7 truncation itself might cause fetal growth restriction as it includes haploinsufficiency of ∼20 biallelically expressed genes located at the telomeric end of distal chromosome 7 ( Oh et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are alternative explanations that must be considered, not in the least that the mouse and human placenta differ substantially both structurally and transcriptionally ( Carter, 2018 ; Soncin et al, 2018 ), which could prevent the accurate modelling of this disorder in mice. The DelTel7 truncation itself might cause fetal growth restriction as it includes haploinsufficiency of ∼20 biallelically expressed genes located at the telomeric end of distal chromosome 7 ( Oh et al, 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms whereby such an invading and multifunctional organ has evolved within each lineage are not well understood, several major driving forces are likely involved in the evolution and diversification of the placental tissues in mammals. These include duplication events followed by gene diversification, rewiring of pre-existing gene regulatory networks, exaptation of endogenous retroviruses, ecological pressures, evolutionary conflict between mother and fetus and genomic imprinting (Frost and Moore, 2010; Kaneko-Ishino and Ishino, 2010; Carter, 2012, 2018; Chuong et al, 2013; Lavialle et al, 2013; Renfree et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any alterations affecting gene expression or posttranslational modification may lead to disorders manifested in pregnancy disorders (Majewska et al 2017 ). Studies of the transcriptome provide knowledge concerning placental evolution and create the opportunity to define specific, common genes engaged in reproductive physiology in eutherians (Hou et al 2012 ; Carter 2018 ). Previous study of the beaver revealed that the number of foetuses affects the placental transcriptome, namely 55 C. fiber transcripts were differentially expressed in placentas originating from twin and triple pregnancies (Lipka et al 2017b ).…”
Section: Discussionmentioning
confidence: 99%